Population dynamics of Bombay duck Harpodon nehereus (Hamilton, 1822) of the Bay of Bengal along Bangladesh coast (Bangladesh Journal of Zoology, 2018)
Population parameters of Harpadon nehereus were estimated using FiSAT-II. length-frequency data collected from different landing centers along the coast of Bangladesh. The Von Bertalanffy growth parameters L∞and K for the species were 45.05 cm and 1.30/year, respectively. The annual rate of natural mortality (M) and fishing mortality (F) were found to be 1.86 and 2.58, respectively. The estimated value of the exploitation rate (E) using the lengthconverted catch curve was 0.58 and E max was found to be 0.582. The recruitment pattern of this species was continuous and two peaks per year. The present investigation clearly showed the over fishing (E > 0.50) condition for H. nehereus in Bangladesh. The estimated length-weight relationship for the combined sex was found to be W = 0.003199 L3.Bangladesh J. Zool. 45(2): 101-110, 2017